Effect of irrigation on the production and volatile compounds of sweet basil cultivars (Ocimum basilicum L.) - Radácsi Péter; Inotai Katalin; Sárosi Szilvia; Hári Katalin; Seidler-Łożykowska Katarzyna; Musie Sintayehu; Zámboriné Éva Németh (Herba Polonica, 2020)
Introduction: Irrigation plays an important role in the cultivation of medicinal plants. There is a lack of information on intraspecific variability of reactions to the effect of drought.